RANCANG BANGUN MONITOR SUHU GAS METANA DAN KARBON DIOKSIDA PADA BIOGAS - Pradigdya, Christian Andrean; Harianto, Harianto; Puspasari, Ira (Journal of Control and Network Systems, 2014)
This paper obtain temperature effect on the level of methane and carbon dioxide in the biogas. For that purpose the author created a monitoring system. The monitoring system built from microcontroller as the main controller of sensors. In order to be complete the monitoring system, a logging data system must be created to provide a reliable data. To obtain temperature effect all data will be analized by certain application.